Problems of mathematics teachers of public secondary schools in Quezon City - Udomphun, Sirisuk 1940-
The respondents were 92 mathematics teachers and 8 mathematics department heads from 8 high schools. The problems regarding teachers assignments which often occur are very big classes, student mobility and teacher mobility. Problems also occur because students lack mastery of the four fundamental operations and the ability to make computations, have difficulty in making generalizations, have poor reading comprehension and are unable to express their ideas mathematically. Teachers also encountered problems due to insufficiency of teaching guides and other curriculum materials.